VALIDITAS DAN RELIABILITAS ANGKET RASA EMPATI - Komarudin, Ranayuda Fujiansyah; Rohaeti, Euis Eti; Yuliani, Wiwin (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
Empathy is the emotional ability to feel the emotions that other people feel. The purpose of this study was to determine the sense of empathy in class VIII MTSN 3 Purwakarta students. The research method used is the development of Borg and Gall. Product validation was carried out by education practitioners and BK teachers, the validity of the instrument was tested on students. In this study took a sample of 23 students. The research instrument used was an empathy questionnaire. Data analysis used product moment validity test and Cronbach's alpha reliability test assisted by SPSS. The results of data analysis showed that all statements were valid because rcount was more than rtable. Cronbach's Alpha coefficient is 0.788 so it is declared reliable in the high category.